Manajemen Orsiwa dalam Menumbuhkan Kesadaran Berorganisasi di Madrasah Aliyah Nurul Jadid Paiton Probolinggo - Abdur Rozaq; Nur Ittihadatul Ummah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the management of the student organization (Orsiwa) at Madrasah Aliyah Nurul Jadid Peminatan Unggulan Keagamaan Paiton Probolinggo and its role in enhancing students' awareness of organization. Orsiwa is an organization managed by students with a structure resembling a government system, consisting of executive, legislative, judicial, and press branches. The research employs a descriptive qualitative approach, with data collection through interviews, participatory observation, and documentation. The subjects of the study include the head of the madrasa, the vice principal for student affairs, the managers and members of Orsiwa, as well as the guiding teachers. The findings indicate that planning, organizing, implementing, and supervising within Orsiwa are carried out effectively, contributing to an increase in students' awareness of organization, the development of leadership skills, and the strengthening of cooperation among members. This structured management also positively impacts the quality of activities and the enhancement of students' character. The study recommends that the existing management system be maintained and further developed as an effective and inspiring model for student organizations.